Sustainable synthesis of silicon nitride nanowires using waste carbon fibre reinforced polymer (CFRP). (1st July 2018) - Farzana, Rifat; Rajarao, Ravindra; Mansuri, Irshad; Sahajwalla, Veena
Abstract: Waste carbon fibre reinforced polymer (CFRP) is challenging to recycle due to its complex composition (i.e fibre, matrix, and filler materials) and is therefore mostly sent to landfill. This study details a novel approach to synthesise silicon nitride (Si3 N4 ) nanowires using CFRP waste as a reducing agent to step forward in sustainability by closing the recycling loop. A vapor-solid mechanism has been proposed to describe the use of waste CFRP as a source of carbon and reducing gas and silica as a source of silicon to synthesise Si3 N4 nanowires under nitrogen atmosphere at 1450 °C. Synthesised Si3 N4 nanowires are in the range of 80–100 nm in diameter and have been confirmed by X-ray diffraction, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, Field emission scanning electron microscopy and transmission electron microscopy analysis. Photoluminescence spectra have provided evidence of a yellow luminescence property of the synthesised Si3 N4 nanowires which may lead to a potential application in optical devices. This novel synthesis of valuable Si3 N4 nanowires using waste CFRP as a reducing agent presents a promising approach of transforming an expensive waste disposal into a profitable resource material. Graphical abstract: Highlights: Novel and sustainable pathway to synthesise Si3 N4 nanowires using CFRP waste. Si3 N4 nanowires were mainly composed of α-Si3 N4 and were 80–100 nm in dimeter. Synthesized Si3 N4 nanowires were confirmed by XRD, FTIR, XPS, EDS, Raman techniques. A vapor-solid mechanism was proposed for the formation of Si3 N4 nanowires. Si3 N4 nanowires showed yellow luminescence property.